2016
DOI: 10.1080/17441692.2015.1132472
|View full text |Cite
|
Sign up to set email alerts
|

The role of social support on HIV testing and treatment adherence: A qualitative study of HIV-infected refugees in southwestern Uganda

Abstract: Little is known about the factors that encourage or discourage refugees to test for HIV, or to access and adhere to HIV care. In non-refugee populations, social support has been shown to influence HIV testing and utilization of services. The present study enrolled HIV-infected refugees on anti-retroviral therapy (ART) in Uganda, who participated in qualitative interviews on HIV testing, treatment, and adherence. Interviews were analyzed for themes about four types of social support: emotional, informational, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Overcoming Barriers Through Disclosure (Social) Life in Nakivale is communal and social. Refugee and Ugandan nationals more easily overcame barriers to engagement in HIV clinic when they had help [31]. For instance, friends and family provided money for transport or child care while the client traveled to clinic.…”
Section: Disclosurementioning
confidence: 99%
“…Overcoming Barriers Through Disclosure (Social) Life in Nakivale is communal and social. Refugee and Ugandan nationals more easily overcame barriers to engagement in HIV clinic when they had help [31]. For instance, friends and family provided money for transport or child care while the client traveled to clinic.…”
Section: Disclosurementioning
confidence: 99%
“…Further, they are disproportionately impacted by economic, legal, and social disadvantage, food insecurity and unequal distribution of goods. Women from a refugee background might also experience a lack of social connectedness and emotional support in their host country (Rouhani et al, 2017), which can increase the stress of family responsibilities. Moreover, women from a refugee background are not always able to flee to safety with their children (Smith, 2015) and this separation increases loss and grief (Schweitzer, Vromans, Ranke, & Griffin, 2014).…”
Section: Challenges Of Women From Refugee Background Living With Hivmentioning
confidence: 99%
“…Various authors [4] [6] [7] [8] [9] proposed methods to explain why the uptake of HIV testing is still below expected levels among youth. Some of these authors identified a lack of knowledge about where to obtain the test, distance to testing site, or financial problems as some key risk factors that hinder HIV testing.…”
Section: Introductionmentioning
confidence: 99%